2009
DOI: 10.4315/0362-028x-72.7.1476
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Formation Ability of Listeria monocytogenes Isolates from Raw Ready-to-Eat Seafood

Abstract: Listeria monocytogenes is of great concern as a foodborne pathogen. Many ready-to-eat foods are widely contaminated with this organism and have caused listeriosis outbreaks and sporadic cases in many countries. In Japan, there is a high incidence of L. monocytogenes contamination, specifically in raw ready-to-eat seafood. Identical L. monocytogenes subtypes have been isolated repeatedly from samples of food manufactured at a given store or processing plant, and researchers suspected that certain L. monocytogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 22 publications
1
34
1
2
Order By: Relevance
“…Previous work showed variable capacities of the strains to form biofilms depending on their lineage (28). Some works showed that lineage I strains produced more biofilms than lineage II strains (15,16), and others reached the opposite conclusion (17,19). In our study, a weak correlation was detected between the strain lineage and the structure of the biofilms.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Previous work showed variable capacities of the strains to form biofilms depending on their lineage (28). Some works showed that lineage I strains produced more biofilms than lineage II strains (15,16), and others reached the opposite conclusion (17,19). In our study, a weak correlation was detected between the strain lineage and the structure of the biofilms.…”
Section: Discussioncontrasting
confidence: 67%
“…Indeed, most published reports focusing on the biofilm formation of several strains are based on global quantitative measurements (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…This has resulted in numerous costly recalls, disease cases, and outbreaks, which are often associated with high mortality (94). As a result, a zero-tolerance policy for L. monocytogenes currently exists for RTE meat and poultry products manufactured in the United States.Specific resident strains of L. monocytogenes have been found to persist for months to more than a decade (70,78,95,105) in various types of food processing plants manufacturing meat products (5, 38, 40, 90, 105), poultry products (4-6, 32, 78, 85), dairy products (4,5,37,48,53,101), seafood products (4,5,73,86,95), vegetables (5), and sandwiches (8) and also in retail environments (88). These persistent strains are genetically distinct from transient strains that are isolated sporadically (4, 5).…”
mentioning
confidence: 99%
“…Entretanto, diferentes estudos têm quantificado os biofilmes em placa de microtitulação baseando-se na quantificação de biomassa, de viabilidade e da matriz dos biofilmes (CHANG et al, 2012;HARVEY;KEENAN;GILMOUR, 2007;PEETERS, NELIS, COENYE;2008;SHAKERI et al, 2007, TAKAHASHI et al, 2009.…”
Section: Biofilmesunclassified
“…O ensaio com placa de microtitulação possui vantagens em relação a outros métodos para avaliar a formação de biofilmes em termos de objetividade, precisão, simplicidade e rapidez para, por exemplo, avaliar as diferenças na formação de biofilmes entre cepas ou determinar a eficácia de biocidas (CHANG et al, 2012;HARVEY;KEENAN;GILMOUR, 2007;PEETERS, NELIS, COENYE;2008;SHAKERI et al, 2007;TAKAHASHI et al, 2009;TRESSE et al, 2007).…”
Section: Biofilmesunclassified